The effects of infrastructure expenditure to the Economic Growth of Central Luzon (1998-2008) - Capili, Crysler Delos Santos; Macaraeg, Adrian; Romero, Jan Miguel Miranda; Roque, Jerson Agamilla
This study presents an analysis of the contribution of infrastructure expenditures, specifically on transport infrastructures, to the economic growth of Central Luzon for the period 1998-2008. This study determines whether or not such expenditures have indeed contributed to the region's investment, employment, and economic growth. Specifically, this paper helps identify if expenditures in transportation infrastructures is really crucial in propelling regional economic growth, and thus help policy makers channel scarce resources to their most efficient and effective uses.